Narcissism between cold-blooded and hot-headed characters in toxic online behaviors. The moderating role of the R4 functional drivers - Mazzeo, Oronzo; La Selva, Giuseppe; Longo, Manuela; Monacis, Lucia (Frontiers in Psychology, 2025)
IntroductionPrevious studies on the association of narcissism with toxic online behaviors have shown mixed results, ranging from a weak relationship with cyberbullying to no relationship with trolling behavior. Moreover, there has been no clear distinction on which specific dimension (grandiose or vulnerable) is related to online aggressive behaviors. Therefore, the present study examined the relationships of the two variants of narcissism with cyberbullying and trolling behavior, taking into account the moderating role of four different functional drivers.MethodThree self-reported questionnaires were administered to 202 undergraduate students. The survey included a sociodemographic section, the grandiose and vulnerable Narcissism dimension, the tendency towards engaging in cyberbullying and/or trolling behaviors, and four functional drivers of cyber-aggression.ResultsFindings indicated individual differences between the two variants of narcissism associated with the two cyber-aggressive behaviors. Correlational analyses showed that (i) vulnerable narcissism was consistently related to cyberbullying and trolling behavior; (ii) grandiose narcissism was neither related to cyberbullying nor to trolling behavior. Moderation analyses indicated that (iii) grandiose narcissists were more likely to show trolling behavior if they exhibited high levels of functional driver (reward and revenge), and were less likely to be engaged in cyberbullying behavior if they displayed lower levels of revenge; (iv) vulnerable narcissists were more likely to show trolling behavior if they manifest high levels of revenge. Finally, the findings reported no other moderated effects of the motivational drivers on cyberbullying behavior for vulnerable narcissists.DiscussionThis study provided evidence for the dual behavioral mode of the variants of narcissism in cyber-aggression, thus discovering the antagonistic aspect underlying both variants of the trait in connection with the four functional drivers. Further studies should not only confirm such empirical evidence, but also develop effective moderation intervention tailored to a more detailed users’ personality profile for reducing trolling and cyberbullying behaviors.